Development and Validation of the Force Diagrams Representation Test - Sirait, Judyanto; Ricky, Patrick; Hamdani, Hamdani (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
Experts and students frequently use force diagrams as a physics representation to understand the force concept. This study aims to develop and validate a force diagram representation test that physics teachers in senior high schools can use. Research and development is implemented in this study by following some steps: analyze, define, design, implement, and evaluate. The 225 senior high school students in Pontianak are involved in this study, from the pilot study to the testing on a large scale. Data analysis includes measuring content validity, reliability index, and parameters of the test using the Rasch model. The test consists of 25 items in a multiple-choice format that cover three contexts: horizontal plane, inclined plane, and hanging object, and covers three situations, including the object being at rest, moving with constant velocity, and moving with constant acceleration. The results show that the content validity test obtained a score of 0.95 for the very good category, and the readability index results obtained a score of 7.42, which means it is easily understood by high school students. Rasch analysis shows that a unidimensional percentage is 30.5%, which means the test is able to measure one ability, and item reliability is 0.98. All items fit the Rasch model and had varying item difficulties. This study indicates that the force diagram representation test (FDRT) can be used by teachers as one of the instruments to measure students’ understanding of force.